2006
DOI: 10.1242/dev.02520
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell migration, transdifferentiation and apoptosis during mouse secondary palate fusion

Abstract: Malformations in secondary palate fusion will lead to cleft palate, a common human birth defect. Palate fusion involves the formation and subsequent degeneration of the medial edge epithelial seam. The cellular mechanisms underlying seam degeneration have been a major focus in the study of palatogenesis. Three mechanisms have been proposed for seam degeneration:lateral migration of medial edge epithelial cells; epithelial-mesenchymal trans-differentiation; and apoptosis of medial edge epithelial cells. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
140
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 25 publications
7
140
1
4
Order By: Relevance
“…Different results, however, have been reported by a third group (Jin and Ding, 2006b), who showed that some mesenchymal -galactosidase activity was present during and immediately after regression of the MES in K14-Cre; R26R embryos. The authors suggested that the discrepancy might have resulted from differences in Cre expression levels and/or patterns in the palatal epithelium in the different K14-Cre transgenic mouse lines used (Jin and Ding, 2006b).…”
Section: Palatal Fusion: Midline Epithelial Seam Dissolutionmentioning
confidence: 63%
See 1 more Smart Citation
“…Different results, however, have been reported by a third group (Jin and Ding, 2006b), who showed that some mesenchymal -galactosidase activity was present during and immediately after regression of the MES in K14-Cre; R26R embryos. The authors suggested that the discrepancy might have resulted from differences in Cre expression levels and/or patterns in the palatal epithelium in the different K14-Cre transgenic mouse lines used (Jin and Ding, 2006b).…”
Section: Palatal Fusion: Midline Epithelial Seam Dissolutionmentioning
confidence: 63%
“…To address this issue, palatal shelves derived from wild-type embryos were recombined in culture with palatal shelves expressing lacZ in all cells (Jin and Ding, 2006b). lacZ-expressing epithelial cells migrated onto the wild-type palatal shelves, indicating that MES migration can occur during palatal fusion.…”
Section: Palatal Fusion: Midline Epithelial Seam Dissolutionmentioning
confidence: 99%
“…Epithelial mesenchymal transition (EMT) plays a crucial role in MES degradation (Greene and Pisano, 2010, Griffith and Hay, 1992, Jalali et al, 2012, Jin and Ding, 2006, Shuler et al, 1992, Yu W, 2009. It is characterized by loss of epithelial cell morphology and acquisition of mesenchymal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The most significantly enriched molecular function was the "transcription factor" (P = Funato N et al . Cleft palates in mice the fusion line by epithelial cell migration, apoptosis, and epithelialmesenchymal transdifferentiation [14] . Tgfb3 (transforming growth factor, beta 3) or Egfr (epidermal growth factor receptor) knockout mice lack the adhesive interactions between the palatal shelves because the fate of MEE cells is altered [1518] .…”
Section: Mouse Models For Studying the Molecular Mechanisms Of Palatamentioning
confidence: 99%